The Fate of Pagan Temples in the Western Part of the Empire in the Late Roman Empire (4th Century). Selected Examples - Piechocka-Kłos, Maria (Studia Warmińskie, 2023)
This publication presents a detailed analysis of the fate of pagan temples located within the Western Roman Empire, particularly in the region of Gaul. The timeframe of the research, due to the vastness and multifaceted nature of the issue, covers only the 4th century. The main thread of the research presented here is primarily the attitude of the ecclesiastical authorities, mainly the bishops, governing the western dioceses and the faithful themselves to the shrines of pagan worship. The research was supplemented by a brief reference to the Roman law in force, i.e. the position of the Christian emperors, which was supported by historical sources on some issues. The analysis of the sources made it possible to conclude that the actions of destroying pagan temples within the Western Roman Empire, were not common and occurred much less frequently than in the East or Africa. Many of them continued to function intact. Some of them were demolished (the activities of St Martin of Tour), some were converted into Christian churches, among others, and there were also some that, abandoned, naturally deteriorated under the influence of adverse weather conditions. The study presented here is a continuation of the author’s research into the issue of pagan temples with regard to the involvement of bishops in the destruction of pagan temples in the east of the Empire in the late Roman Empire (4th to 5th century).